GRB 230911A: The First Discovery of a Fermi GRB Optical Counterpart with the Gravitational-wave Optical Transient Observer (GOTO) - Belkin, S.; Gompertz, B. P.; Kumar, A.; Ackley, K.; Galloway, D. K.; Jiménez-Ibarra, F.; Killestein, T. L.; O’Neill, D.; Wiersema, K.; Malesani, D. B.; Levan, A. J.; Lyman, J.; et al. (Institute of Physics Publishing, 2025)
We report on the detection of candidate optical counterpart GOTO23akf/AT2023shv to the GRB 230911A with the Gravitational-wave Optical Transient Observer (GOTO) instruments located at La Palma, Canary Islands, and Siding Spring Observatory, Australia. The Fermi Gamma-ray Burst Monitor, which finds gamma-ray bursts (GRBs) nearly every two days, detected GRB 230911A with a statistical uncertainty of 4fdg1. However, the large (∼10–100 deg2) localization areas mostly impede the rapid identification of an optical counterpart. GOTO facilities fully covered 90% localization area of the GRB 230911A. We proposed GOTO23akf as the optical afterglow of GRB 230911A, subsequently confirmed through Swift-X-Ray Telescope observations in which an uncatalogued X-ray source spatially coincident with the GOTO candidate was detected. This is the first optical afterglow discovery for a Fermi GRB with the newly expanded GOTO network.